Aktivitas Mukolitik Ekstrak Etanol Kulit Buah Jeruk Sambal (Citrus amblycarpa (Hassk.) Ochse) Secara In Vitro - DINA YUSPITA SARI; Sanitasari; Ratna Widyasari (Akademi Farmasi Yarsi Pontianak, 2022)
An in vitro study of the mucolytic activity of the ethanol extract of limau citrus peel (Citrus amblycarpa (Hassk.) Ochse) has been carried out. This study aims to prove the mucolytic activity of the ethanol extract of limau citrus peel in vitro and determine the appropriate concentration. The mucolytic activity was tested using a Brookfield viscometer with 5 treatments and 3 repetitions every 15 minutes for 1 hour with different concentrations, namely: positive control (0.2% Acetylcysteine), negative control (0.5% Na-CMC), and ethanol extract of limau citrus peel with concentrations of: 1.6%, 2.1%, and 2.6%. The results of this study show that the percentage of mucolytic activity in extracts with concentrations of 1.6%, 2.1%, and 2.6% were 4.108%, 9.906%, and 16.952%. The results indicate that the three extract concentrations provide mucolytic activity.